Analysis of Factors Guests Consider for Eating and Drinking at Gloria Jean's Coffee - Nyoman Wiantara, I Gusti (Akademi Komunitas MAPINDO, 2023)
Tourism includes various service industries needed by tourists during their trips and temporary stays in the tourist destinations visited. Coffee shop is a type of business that is currently booming in Indonesia, especially in Bali. The purpose of this study was to find out the factors considered by guests to eat and drink at Gloria Jean's Coffee and to find out the dominant factors influencing guests' interest to eat and drink at Gloria Jean's Coffee. This research was conducted at Gloria Jeans Coffees with respondents totaling 100 respondents, the sample in this study was selected using the accidental sampling method. The data in the study were analyzed using exploratory factor analysis which was supported by the SPSS version 17.0 for windows statistical program. The results of this study are: 1) the explanation of each factor that becomes the guest's perception of eating and drinking at Gloria Jeans Coffees is the percentage considered by tourists in choosing Gloria Jeans Coffees of 78.521% can be explained by these three factors, namely factor 1 is called the advantage factor, factor 2 is called the supporting factor, factor 3 is called the image factor, and factor 4 is called the product and convenience factor. 2) Thus it can be concluded on these advantages factors that determine tourists choose Gloria Jeans Coffees are easy-to-reach locations, affordable food and beverage prices, information complexity, easy information, food and beverage lists according to standards with other Gloria outlets, complete facilities, employee ability to handle guest complaints, employee appearance, employee service and employee communication skills. 3) The supporting factors are formed by a strategic location, security, cleanliness and impressions from guests. 4) The image factor is formed by the employee's ability variable in handling guest complaints, employee friendliness variables and image variables. 5) the product and convenience factors are formed by the variable quality of food and beverages sold to consumers and the variables offered in the packages as well as the convenience variable. Keywords: Factor analysis, Perception, Coffee Shop